2020
DOI: 10.1177/1098300720951940
|View full text |Cite
|
Sign up to set email alerts
|

Examining Commitment to Prevention, Equity, and Meaningful Engagement: A Review of School District Discipline Policies

Abstract: Although there is increasing awareness of policy decisions contributing to disproportionality in exclusionary practices, few studies have empirically examined common elements of discipline policies across the nation. We utilized a methodological review and the Checklist for Analyzing Discipline Policies and Procedures for Equity (CADPPE) to examine the extent to which current policies reflect recommendations from research regarding best practices for encouraging appropriate behaviors and preventing undesired b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…Although there are generally two types of suspensions (ISS and OSS) and millions of students receive ISS nationwide, only a handful of studies focus on ISS or differentiate between the two suspension types (Anderson et al, 2019;Anyon et al, 2021;Cholewa et al, 2018;Jabbari & Johnson, 2020;Noltemeyer et al, 2015;Smith et al, 2021). Even though a growing number of studies are including both ODRs and suspensions as outcomes in the same study (Anyon et al, 2014(Anyon et al, , 2016Bradshaw et al, 2010;Nishioka et al, 2021;Vincent & Tobin, 2011), within the robust school discipline literature, most studies tend to focus on either ODRs (Cook et al, 2018;Gion et al, 2020;Gregory et al, 2014Gregory et al, , 2019 or suspensions (Green et al, 2021;Gregory et al, 2018;Hashim et al, 2018;Lacoe & Steinberg, 2018).…”
Section: The Dimensions Of School Discipline: An Analytic Frameworkmentioning
confidence: 99%
“…Although there are generally two types of suspensions (ISS and OSS) and millions of students receive ISS nationwide, only a handful of studies focus on ISS or differentiate between the two suspension types (Anderson et al, 2019;Anyon et al, 2021;Cholewa et al, 2018;Jabbari & Johnson, 2020;Noltemeyer et al, 2015;Smith et al, 2021). Even though a growing number of studies are including both ODRs and suspensions as outcomes in the same study (Anyon et al, 2014(Anyon et al, , 2016Bradshaw et al, 2010;Nishioka et al, 2021;Vincent & Tobin, 2011), within the robust school discipline literature, most studies tend to focus on either ODRs (Cook et al, 2018;Gion et al, 2020;Gregory et al, 2014Gregory et al, , 2019 or suspensions (Green et al, 2021;Gregory et al, 2018;Hashim et al, 2018;Lacoe & Steinberg, 2018).…”
Section: The Dimensions Of School Discipline: An Analytic Frameworkmentioning
confidence: 99%
“…One conclusive point found in the report was that each of the states gave the authority to local education agencies to craft the provisions needed to conduct school discipline at the school level; however, the enactment of policies on school discipline alternatives can “enable conditions for effective implementation by providing support and ensuring accountability,” (Rafa, 2019, p. 8). Finally, Green et al (2020) examined the connection between research on affirmative disciplinary practices in school discipline policies for all 50 states and the District of Columbia. In their findings, Green and colleagues found that while states had their distinct policies, the 147 school districts included in their sample did not have explicit policies that included research-based recommendations, such as CRCM, for reducing exclusionary discipline practices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In their findings, Green and colleagues found that while states had their distinct policies, the 147 school districts included in their sample did not have explicit policies that included research-based recommendations, such as CRCM, for reducing exclusionary discipline practices. Rafa (2019), Curran (2019, 2020), and Green et al (2020) illuminate the fact that in the absence of explicit governance, school districts can enforce stricter school discipline policies than what is necessary to curtail unwanted student behavior. In light of such strictness, the alternative supposition is plausible: school districts are more likely to follow specific guidance regarding school discipline if such policies are legalized by their state legislators or state board of education.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Policies should be constructed and implemented to create accountability for the continuous application of activities that explicitly uphold and promote racial justice at all levels. These include several strategies such as district discipline policy reform to incorporate proactive evidence‐based strategies (Green et al, 2020); discipline data disaggregation and consultation procedures for school staff that reduce racial disparities in discipline and positive reinforcement (Gion et al, 2020); effective prejudice reduction programs for students (Grapin et al, 2019) and staff (Whitford & Emerson, 2019); and culturally responsive teaching (Larson et al, 2018). Given the apparent impact of microaggressions on suicidality (Madubata et al, 2019), empirically validated methods for addressing microaggressions in educational contexts are greatly needed.…”
Section: Ecosocial Pathways For Suicidality In Black Youth Within Sch...mentioning
confidence: 99%